Urban–Rural Differences in Sustainable Energy Consumption Behavior: Evidence from Indonesia - Istiqomah, Nurul; Mafruhah, Izza; Gravitiani, Evi; Rahmawati, Fauziyah Nisa (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study offers a novel contribution by integrating micro-level spatial comparison and behavioral analysis. Unlike previous studies that highlight income or education as key drivers, this research finds that structural factors have a stronger influence on energy-saving behavior. Research Objectives: This study aims to examine household energy consumption patterns and identify the socioeconomic and structural determinants of energy-saving behavior in urban and rural settings. Research Methods: A mixed-methods approach is employed. Qualitative analysis using ATLAS.ti explores household energy-use practices and perceptions, while binary logit regression is applied to identify factors influencing energy-efficient behavior. Empirical Results: The results indicate significant differences in energy consumption between urban and rural households. Urban households tend to consume more energy due to lifestyle characteristics and appliance ownership. Regression results show that household size, dwelling area, installed electrical capacity, and residential location significantly affect the likelihood of adopting energy-saving behavior. Rural households exhibit a higher propensity for energy-efficient practices, mainly due to limited electricity access and reliance on traditional energy sources. Implications: Energy policies should incorporate spatial and socioeconomic dimensions, reduce subsidy-induced price distortions, and promote incentives for energy-efficient behavior and renewable energy adoption. JEL Classification: J41, J42, D12, R20